SERIAL TELEVISI DEXTER SEBAGAI ANAKRONISME DALAM SASTRA POPULER - Ida Rochani Adi (LITERA, 2014)
In the popular literature context, this study aims to investigate: (1) how the formulation of the characterization of Dexter in the television serial Dexter violates the tradition of literary characterization, and (2) how the formula of moral values is dramatized through Dexter, who is a sociopath, psychopath, serial killer, and person without moral. The research object was the television serial Dexter, which ranks five in popularity in the world. The data were collected by documenting 84 episodes of the serial having been broadcast since 2006. They were analyzed by means of content analysis and qualitative descriptive techniques. Based on the findings, the conclusions are as follows. First, there is a violation or anachronism of characterization through the main character in the serial. Second, the dramatized moral values still contain conventional values although they are in different forms.